(untitled) (Journal of Mathematical Study, 2018)
This paper deals with numerical methods for the Maxnear criterion of multiple-sets canonical analysis. Optimality conditions are derived. Upper and lower bounds of the optimal objective function value are presented. Two iterative methods are proposed. One is an alternating variable method, and the other called Gauss-Seidel method is an inexact version of the alternating variable method. Convergence of these methods are analyzed. A starting point strategy is suggested for both methods. Numerical results are presented to demonstrate the efficiency of these methods and the starting point strategy.